Assessing the Validity of Voice Stress Analysis (VSA) Tools in a Jail Setting in Oklahoma City, Oklahoma, 2006 - Damphousse, Kelly R. ([Verlag nicht ermittelbar], 2008)
The purpose of the project was to assess the validity of two Voice Stress Analysis (VSA) tools currently on the market: the Layered Voice Analysis (LVA) and the Computer Voice Stress Analyzer (CVSA). The methodology and sampling protocols for this study were derived from the pre-existing methodology and sampling techniques employed in the National Institute of Justice-funded Arrestee Drug Abuse Monitoring (ADAM) program that operated in Oklahoma County from 1998 to 2004. The researchers interviewed arrestees in the Oklahoma County jail about their recent illicit drug use during the months of February and March 2006. The VSA data collected using each of the software systems in this study were sent to certified examiners from CVSA and LVA for their analysis. After the completion of the interview, the subjects were asked to complete the data collection process by supplying urine specimens. Answers from the 319 respondents were compared to the results of a urinalysis test to determine the extent to which they were being deceptive. Then, their "actual deceptiveness" was compared to the extent to which deception was indicated by the VSA programs. The dataset contains (1) demographic information obtained from the official booking records, (2) responses to survey questions about recent drug use, (3) the results of a urinalysis test on five drugs, (4) variables recording "deception" or "no deception" on each of the drugs, and (5) decisions by novice and expert analysts regarding the indication of deception.